Grammatica diacronica del napoletano - Ledgeway, Adam (Beihefte zur Zeitschrift für romanische Philologie ;, 2009)
A rich and long literary tradition (dating back as early as the late 13th century), coupled with an abundance of diachronic and synchronic variation, affords Neapolitan a privileged position amongst the Romance languages, offering the Romance linguist a rare opportunity to explore the structural evolution of one of the lesser known Romance varieties. Yet, while evidence from other Romance languages and dialects has had a profound influence on the development of theoretical issues relating to language structure, variation and change, references to Neapolitan are conspicuous by their absence, si.